2001
DOI: 10.2105/ajph.91.9.1435
|View full text |Cite
|
Sign up to set email alerts
|

Psychologic Distress and Natural Menopause: A Multiethnic Community Study

Abstract: Psychologic distress is associated with irregular menses in midlife. It is important to determine whether distress is linked to alterations in hormone levels and to what extent a mood-hormone relationship may be influenced by socioeconomic and cultural factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
137
1
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(159 citation statements)
references
References 41 publications
11
137
1
10
Order By: Relevance
“…Since mild emotional symptoms occur in many women during the perimenopausal years, it is important to establish whether the symptoms are of suicient severity and duration to constitute major depression, generalized anxiety disorder, or panic disorder. Psychological distress is usually seen more in females with disturbed sleep [11]. Sleep could be disturbed in midlife due to psychosocial stressors of life or as a result of symptoms of menopause like hot lushes (also termed as "lashes") and night sweats.…”
Section: Secondary Efects On Mood/psychiatric Morbidity and Menopausementioning
confidence: 99%
“…Since mild emotional symptoms occur in many women during the perimenopausal years, it is important to establish whether the symptoms are of suicient severity and duration to constitute major depression, generalized anxiety disorder, or panic disorder. Psychological distress is usually seen more in females with disturbed sleep [11]. Sleep could be disturbed in midlife due to psychosocial stressors of life or as a result of symptoms of menopause like hot lushes (also termed as "lashes") and night sweats.…”
Section: Secondary Efects On Mood/psychiatric Morbidity and Menopausementioning
confidence: 99%
“…34 Findings from the SWAN study have shown a correlation between the perimenopause and increased risk of depressed mood when compared with women who are premenopausal. 35 Women in perimenopause, who have the greatest fluctuations in sex steroid hormones, are particularly likely to report menopausal symptoms including sleep disturbance, psychological symptoms, and vasomotor symptoms. 36 It can be difficult to tease out separate effects of age versus menopausal status.…”
Section: Depressed Mood Sleep and Sexual Problems In Swanmentioning
confidence: 99%
“…A series of SWAN studies evaluated menopausal status in relation to outcomes of dysphoric mood [48,52], depressive symptoms (CES-D) [53][54][55] and depressive disorder [56,57]. These studies overall showed that depressive symptoms and dysphoric mood varied by menopausal status and were independent of other known risk factors for depression.…”
Section: Depression and The Menopause Transitionmentioning
confidence: 99%